2017
DOI: 10.1016/j.sjbs.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of olive and juniper leaves extracts on nephrotoxicity induced by thioacetamide in male mice

Abstract: This study, for the first time, evaluates the effect of olive and juniper leaves extracts and their combination on thioacetamide (TAA)-induced nephrotoxicity in male mice. The experimental mice were divided into eight groups. Group 1 was served as control. Group 2 was exposed to TAA. Group 3 was treated with TAA and olive leaves extract. Group 4 was subjected to TAA and juniper leaves extract. Group 5 was exposed to TAA and olive and juniper leaves extracts. Groups 6, 7 and 8 were treated with olive, juniper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…The olive tree (Olea europaea), family: Oleaceae, and in particular, its leaves have been used for the treatment of wounds, fever, diabetes, gout, atherosclerosis, and hypertension since ancient times [163]. In the Mediterranean area, olive leaves are one of the by-products of farming of the olive grove; they can be found in high amounts in the olive oil industries and they accumulate during pruning of the olive trees [164].…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…The olive tree (Olea europaea), family: Oleaceae, and in particular, its leaves have been used for the treatment of wounds, fever, diabetes, gout, atherosclerosis, and hypertension since ancient times [163]. In the Mediterranean area, olive leaves are one of the by-products of farming of the olive grove; they can be found in high amounts in the olive oil industries and they accumulate during pruning of the olive trees [164].…”
Section: Olive Tree (Olea Europaea)mentioning
confidence: 99%
“…The kidney is known to be hugely susceptible to damage caused by various toxic elements as large volume of blood flows through it and the toxins filtered usually gets concentrated in the kidney tubules [36]. High protein content in urea known as Proteinuria is a urine marker which is a common indicator for various kidney pathologies and dysfunction [37].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that single dose administration of TAA to the experimental animals significantly increased serum uric acid (mg/dL), urea (mg/dL), creatinine (mg/dL), while there was no significant alteration serum level of calcium (mg/dL), magnesium (mg/dL), and phosphorus (mg/dL) level as compare to the rats of normal control animals (Figures 4 and 5). These changes are clear indication of an acute nephrotoxicity [8,41,42].…”
Section: Impression Of Novel Treatment On Uric Acid Urea Creatininementioning
confidence: 97%
“…Additionally, TAA also causes damage to the kidney, brain, stomach, intestine, spleen and lungs. Increased level of serum uric acid, urea and creatinine are marker of the impairment in kidney functions and kidney toxicities [8].…”
Section: Biomedical Research 2018; 29 (15): 3106-3116mentioning
confidence: 99%